2009
DOI: 10.1063/1.3077202
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime recovery in ultrahighly titanium-doped silicon for the implementation of an intermediate band material

Abstract: The doping of conventional semiconductors with deep level (DL) centers has been proposed to synthesize intermediate band materials. A recent fundamental study of the nonradiative recombination (NRR) mechanisms predicts the suppression of the NRR for ultrahigh DL dilutions as a result of the delocalization of the impurity electron wave functions. Carrier lifetime measurements on Si wafers doped with Ti in the 1020–1021 cm−3 concentration range show an increase in the lifetime, in agreement with the NRR suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 19 publications
5
77
0
Order By: Relevance
“…16 2 show the sheet resistance and Hall mobility, respectively, as a function of the absolute temperature (90-380 K) for the three different implantation doses and a nonimplanted substrate that will act as reference. The figures also include the fitting curves resulting from the model that will be described in Sec.…”
Section: Methodsmentioning
confidence: 99%
“…16 2 show the sheet resistance and Hall mobility, respectively, as a function of the absolute temperature (90-380 K) for the three different implantation doses and a nonimplanted substrate that will act as reference. The figures also include the fitting curves resulting from the model that will be described in Sec.…”
Section: Methodsmentioning
confidence: 99%
“…However, experiments have shown that implanting larger doses of titanium in silicon results in lower SRH recombination 44 .…”
Section: Bulk Ib Materials and Solar Cellsmentioning
confidence: 99%
“…In this way, the laser thermal annealing ͑LTA͒ process could be a technological key to obtain an IB in bulk semiconductors. 10,[14][15][16] The effect of the LTA process on III-V semiconductors has been reported previously. 17 However, as far as we are concerned no detailed study has been carried out on GaP.…”
Section: Introductionmentioning
confidence: 99%